A Primer on Small Group Instruction in Undergraduate Mathematics. Issue 10 (26th November 2018) - Reinholz, Daniel L.
Abstract: Increasing evidence supports the use of small group instruction to enhance student learning in undergraduate mathematics. However, effectively enacting such learning methods requires instructors to develop new skills as educators. This paper provides a practical guide for group work in undergraduate mathematics, describing key aspects of group work through the lenses of forming, norming, storming, and performing. I provide vignettes from my own teaching for reference.